INFLUENCE OF bFGF, SDF-1α, OR VEGF INCORPORATED INTO TUBULAR POLYMER SCAFFOLDS ON THE FORMATION OF SMALL-DIAMETER TISSUE-ENGINEERED BLOOD VESSEL IN VIVO - L. V. Antonova; V. V. Sevostyanova; A. G. Kutikhin; Е. A. Velikanova; V. G. Matveeva; T. V. Glushkova; A. V. Mironov; E. O. Krivkina; O. L. Barbarash; L. S. Barbarash (Вестник трансплантологии и искусственных органов)
Aim. To evaluate the potential synergistic effects of basic fi broblast growth factor (bFGF) and stromal cell-derived factor-1α (SDF-1α) complemented with VEGF compared to VEGF alone when being added into poly(3-hydroxybutyrateco-3-hydroxyvalerate) / poly(ε-caprolactone) vascular grafts implanted into rat abdominal aorta for 3, 6, or 12 months.Materials and methods. Utilizing emulsion electrospinning, we fabricated one-layer vascular grafts with either VEGF, bFGF, or SDF-1α, and two-layer vascular grafts with VEGF incorporated into the inner layer and bFGF and SDF-1α incorporated into the outer layer following structural evaluation, tensile testing, and in vivo testing using a rat abdominal aorta replacement model.Results. Grafts containing all three growth factors had a 100% primary patency rate. The combination of bFGF, SDF-1α and VEGF improved morphology and mechanical properties of the grafts. Furthermore, such combination of the bioactive factors promoted endothelialization compared to VEGF alone. In addition, bFGF induced a rapid formation of a SMC layer.Conclusion. Taking together, these fi ndings show that the incorporation of bFGF and SDF-1α into the vascular grafts in combination with VEGF enhances vascular tissue regeneration and provides a higher primary patency rate.